Computer programs for the assembly of DNA sequences. - Gingeras, T R (1979)
A collection of user-interactive computer programs is described which aid in the assembly of DNA sequences. This is achieved by searching for the positions of overlapping common nucleotide sequences within the blocks of sequence obtained as primary data. Such overlapping segments are then melded into one continuous string of nucleotides. Strategies for determining the accuracy of the sequence being analyzed and reducing the error rate resulting from the manual manipulation of sequence data are discussed. Sequences mapping from 97.3 to 100% of the Ad2 virus genome were used to demonstrate the performance of these programs.